Pertumbuhan UMKM Kuliner di Kecamatan Medan Baru: Studi Kasus Warung Cirasa dan Warung Dimsum 66 - Yohanna Dwi Simaremare; Nesmada Putri Manullang; Ondo Apostel Purba; Rotua Sahat Pardamean Simanullang (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to analyze the factors influencing the growth of culinary micro, small, and medium enterprises (MSMEs) in Medan Baru District through a case study of Warung Cirasa and Warung Dimsum 66, located in the University of North Sumatra area. The differences in growth patterns between the two MSMEs form the basis of this study. The method used is a qualitative descriptive approach with data collection techniques in the form of structured interviews, field observations, and document reviews. Primary data were obtained from business owners and documentation of operational activities. The results show that Warung Cirasa experienced stable growth by emphasizing consistent product quality and service, while Warung Dimsum 66 showed relatively rapid growth through the use of digital marketing and viral marketing strategies. The main factors influencing MSME growth include product quality, marketing strategy, business location, and adaptability to market changes. These findings emphasize the importance of integrating product quality and digital marketing innovation to encourage the sustainable growth of culinary MSMEs amidst dynamic competition.